2021
DOI: 10.3389/fpsyg.2021.767886
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Achievement Goal Orientations, Learning Engagement, and Academic Adjustment in Freshmen: Variable-Centered and Person-Centered Approaches

Abstract: Academic adjustment is a principal determining factor of undergraduate students’ academic achievement and success. However, studies pay little attention to freshmen’s antecedent variables of academic adjustment. This study aimed to examine the mechanisms underlying the relationship between achievement goal orientations and academic adjustment in freshmen using variable- and person-centered approaches. A sample of 578 freshmen (aged 18.29±1.04years, 58.5% female) completed questionnaires on achievement goal ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 104 publications
0
15
0
2
Order By: Relevance
“…As for academic factors, variables that were found to be associated with students' academic adjustment were learning engagement and goal orientations (Wang et al, 2021 ), intention to drop out and academic self-efficacy (Girelli et al, 2018 ), and high school GPA and obtained credit points (van der Zanden et al, 2019 ). Considering individual factors, several other variables were found to be associated with students' academic adjustment.…”
Section: Resultsmentioning
confidence: 99%
“…As for academic factors, variables that were found to be associated with students' academic adjustment were learning engagement and goal orientations (Wang et al, 2021 ), intention to drop out and academic self-efficacy (Girelli et al, 2018 ), and high school GPA and obtained credit points (van der Zanden et al, 2019 ). Considering individual factors, several other variables were found to be associated with students' academic adjustment.…”
Section: Resultsmentioning
confidence: 99%
“…To date, most studies investigating the relationship between self-regulated learning and learning engagement in online learning environments have employed a variable-centered approach, which does not account for potential variability and differences in variables between individuals ( Wang et al, 2021 ). Instead, as a person-centered analysis technique, the latent profile analysis (LPA) groups individuals into latent classes or profiles or subgroups according to the correlations on self-regulated learning ( Luo et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Clinical nursing teachers' engagement is important to ensure teaching quality. This study found a medium level of engagement among clinical nursing teachers, higher than Jordanian nurses,28 and lower than Chinese and Portuguese nurses9,29 and Chinese university teachers 30. To be more specific, dedication domain scored the highest and absorption domain scored the lowest.…”
Section: Discussionmentioning
confidence: 62%
“…This study found a medium level of engagement among clinical nursing teachers, higher than Jordanian nurses, 28 and lower than Chinese and Portuguese nurses 9,29 and Chinese university teachers. 30 To be more specific, dedication domain scored the highest and absorption domain scored the lowest. As a whole, our results indicated that clinical teachers' engagement still had much room to improve.…”
Section: Discussionmentioning
confidence: 99%